Back Cover: Ladder‐type Heteroarenes: Up to 15 Rings with Five Imide Groups (Angew. Chem. Int. Ed. 33/2017). Issue 33 (7th July 2017) - Wang, Yingfeng; Guo, Han; Ling, Shaohua; Arrechea‐Marcos, Iratxe; Wang, Yuxi; López Navarrete, Juan Teodomiro; Ortiz, Rocio Ponce; Guo, Xugang
Abstract : A series of imide‐functionalized ladder‐type heteroarenes are reported by R. P. Ortiz, X. Guo, et al. in their Communication onpage 9924 ff . Efficient synthetic routes were developed to construct electron‐deficient fused backbones with multiple imide groups, well‐defined structures, precisely controllable conjugation lengths, and tunable optoelectrical properties.